Improving mechanical properties of Mg–Zn-Nd-Zr alloy by low alloying with Yb and corresponding strengthening mechanisms - Zhaobin Zhang; Jonghyun Kim; Heng Pu; Shuai Zhou; Yaobo Hu; Guangsheng Huang; Bin Jiang; Fusheng Pan (Journal of Materials Research and Technology)
This study was aim to explore the possibility of adding Yb element to Mg–6Zn-3Nd-0.5Zr alloy to develop a commercial high-strength Mg alloy under the condition of low rare earth content. A systematic investigation was conducted and it was shown that the phase compositions were changed by the Yb addition (0–2 wt%). The Mg–Zn phases disappeared while a new phase, (Nd,Yb)Zn2, were formed. The volume fractions of precipitates increased with increasing Yb content. Due to the extra precipitation through the process of extrusion, the volume fractions of precipitates of as-extruded alloys were slightly higher than that of the as-cast alloys. All as-extruded alloys displayed the same strong fiber texture with the (10 1‾ 0) perpendicular and the [1‾ 100] parallel to the extrusion direction. The Yb addition improved the DRX degree, but has little effect on grain orientations, and adjusted the texture intensities by influencing DRX process. When the Yb content is 1.0 wt%, the alloy showed best mechanical properties, with the yield strength and ultimate tensile strength of 400 MPa and 407 MPa. The high strength is the result of the combined effects of excellent grain boundary and texture strengthening.